Implementation of Customer Journey Mapping in Indonesia’s Tourism Industry to Enhance Tourist Satisfaction - Iwan Harsono; Mutia Nasution; Koesmawan Koesmawan (The Eastasouth Management and Business, 2025)
This study explores the implementation of Customer Journey Mapping (CJM) within the Indonesian tourism industry and its impact on enhancing tourist satisfaction. Utilizing qualitative analysis with six key informants representing diverse roles in the industry, the research investigates the level of awareness, challenges, and opportunities associated with CJM practices. The findings reveal that while larger organizations employ CJM to streamline customer experiences, smaller operators face significant barriers such as resource limitations and fragmented collaboration. Key factors influencing tourist satisfaction include accessibility, service quality, and cultural authenticity. The study identifies opportunities for improvement through technology adoption, capacity building, and stakeholder collaboration. These insights underline the potential of CJM as a strategic tool to elevate service delivery, enhance customer satisfaction, and promote sustainable growth in the Indonesian tourism sector.